x^2 -10x =11

Now we will add and subtract [(X's coefficient)/2]^2

We know that X's coefficient is 10

==> Then, we will add (10/2)^2 = 5^2 = 25 to both sides.

==> x^2 -10x +25 = 11 + 25

==> x^2 -10x +25 = 36

Now we will rewrite the expression as a complete square.

==> (x-5)^2 = 36

Now to solve, we will take the square root of both sides.

==> l x -5 l = l6l

==> x-5 = 6 ==> x = 11

==> -(x-5) = 6 ==> -x+5 = 6 ==> -x = 1 ==> x = -1

Then we have two solutions:

**x = { -1, 11}**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now